Using Using Brief Experimental Analysis to Increase Food Consumption for an Adult with an Eating Disorder: A Case Study - Axelrod, Michael (Advances in Social Sciences Research Journal, 2020)
The present study investigated the utility of brief experimental analysis applied to reinforcer assessments in providing a data-based course of treatment targeting food consumption for an adult with Anorexia. Results of two brief experimental analyses indicated the subject consumed more grams of food during the contingent positive attention condition when compared to three other conditions. A brief extended analysis based on the results of the experimental analyses found that positive attention increased the subject’s food consumption during lunch and dinner. Results provide preliminary evidence for using brief experimental analyses for identifying contingent relationships between food consumption and maintaining reinforcers. This might be helpful for those developing prescriptive treatments to increase food consumption of adults with Anorexia.